“I” and “Other”: In Light of Phenomenological-Hermeneutics Reflection - Rebes, Marcin (2022)
The book addresses one of the fundamental questions posed in both the social sciences and the humanities, namely the question of identity and the role played by the “Other” in its construction. The issues analysed in the book are also very topical. Nowadays, when as a result of a number of processes it is more and more difficult to answer the question of identity, both in the individual and collective aspect, such questions become especially actual, and answers to them are provided by particular authors in their erudite articles, referring to canonical texts for Western culture. What makes this publication particularly relevant is the fact that the discussion concerns the figure of the “Other” and its role in identity formation. Admittedly, such analyses have a long academic tradition, the issue seems particularly topical today. The contemporary world is characterised by high mobility, as a consequence of which contacts with the “Other” are now more common and everyday than ever before.Paweł Kubicki